The Role and the Importance in Choosing the Proper Managerial Accounting Concepts Regarding the Need for Information on the Decision Making Factors within the Companies - David, Delia; Dragoș (Coman), Dorica; Pușcaș, Adriana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Both the theory and modern practice of the management accounting took over two general concepts regarding its organizational process, structuring accounting in either an integrated system or a dualist one. We aim at emphasizing the characteristics, the role and the importance of these concepts in regards to the calculation process and the accounting entries of the costs generated by economic entities with an eye at gaining profit. Choosing one of the previously mentioned concepts must be done taking into consideration the specific of the company in question as well as the information necessary to the manager who needs to find out the optimum solution in order to achieve the rehabilitation and efficiency of the activity which is supposed to be carried out. The subject of this work is approached both theoretically and practically, relying on the following research methods: the comparison method, the observation method and the case study method.